Factors Influencing Iron Supplement Consumption Among Adolescent Girls at SMAN 1 Tumijajar - Novaria, Elsya; adinda (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
Iron supplement consumption is an effort to prevent and address iron deficiency anemia in adolescent girls. A pre-survey at SMAN 1 Tumijajar revealed that 0.06%, or 30 female students, requested and consumed iron supplements in the health center (UKS) between January and April. Several factors that may influence iron supplement consumption among adolescent girls include knowledge, attitudes, peer influence, and family support. The objective of this study was to determine the factors influencing iron supplement consumption among adolescent girls at SMAN 1 Tumijajar, West Tulang Bawang Regency, in 2024. The study used a quantitative, observational analytical design with a cross-sectional approach. The sample consisted of 93 female students at SMAN 1 Tumijajar, West Tulang Bawang Regency, using a proportional random sampling technique. Data collection used questionnaires completed directly by the respondents. Univariate and bivariate analyses were conducted using the Chi-Square test. The results of the study showed that most female students did not consume iron-boosting tablets as many as 58 people (62.4%), respondents' knowledge was poor as many as 48 people (51.6%), attitudes were in the good category as many as 53 people (57.0%), the influence of friends was in the supportive category as many as 52 people (55.9%) and family support was in the supportive category as many as 50 people (53.8%). There was an influence of knowledge (p-value = 0.006 and OR = 3.804), attitude (p-value = 0.005 and OR = 3.761), the influence of friends (p-value = 0.009 and OR = 3.474) and family support (p-value = 0.002 and OR = 4.478) on the consumption of iron-boosting tablets. It is hoped that the principal can take policies to improve the SEPEKAN Program (schools concerned about anemia cases) such as activating adolescent health cadres (KKR) for the distribution of TTD.